Peran Pemerintah Daerah Dalam Pelaksanaan Tata Pemerintahan Yang Baik (Good Governance) Dalam Perspektif Hukum - Lala Anggina Salsabila; Dina Pratiwi BR Tambun; Annisa Puspita Sari Batubara (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This article aims to examine the role of regional government in implementing good governance from a legal perspective. The role of Regional Government in the Implementation of Good Governance from a Legal Perspective is a very relevant issue in the context of public administration and law in many countries. As society's demands for quality, transparent, accountable and fair public services become increasingly complex, the concept of good governance becomes very important. This research use desciptive qualitative approach. The data collection technique used is library study, which means reading and understanding the content of discussions and various types of culture from newspapers, tabloids, journals, physical books and ebooks. Good governance aspires to create a government with principles such as transparency (openness), accountability, participation, justice and independence, with the hope of achieving the greatest goals for the prosperity and progress of the people and the country.